Perbedaan hasil pemeriksaan jumlah koloni bakteri pada daging ayam broiler dengan pemberian parutan serai (Cymbopogon citratus) setelah 24 jam - Saadah Siregar; Vincentia Ade Rizky; Wenda Putri Natal Saragih (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Chicken meat is one of the most highly nutritious foodstuffs, as it contains nutrients that are indispensable to the human body, such as water, protein, fat, and other organic ingredients. However, the availability of these complete nutrients has caused the meat to become a medium for bacterial growth. Pathogenic bacteria and spoilage bacteria can cause health problems.Objectives: The study aims to determine the difference in examining the number of bacterial colonies in broiler chicken meat by giving lemongrass (Cymbopogon citratus) after 24 hours.Methods: Quantitative research using experimental design through laboratory testing, namely by determining whether or not there is a decrease in the number of germs in broiler chicken meat by giving grated lemongrass leaves after 24 hours. The sample is broiler chicken meat. The research was conducted in 2021. Laboratory testing was carried out using the pour plate method for two repetitions. Each plate of the dilution is calculated as the number of colonies by multiplying the dilution per 1 gram / 1 ml sample. Data were analyzed descriptively and bivariate using Independent T-test at 95% CI.Results: It was found that the growth of total germ numbers in chicken meat without incubation after 24 hours was treatment one was 39,96 x 106 CFU/gram, and treatment two was 39,87 x 106 CFU/gram, while chicken meat incubated for 24 hours was treatment one. The number of colonies in the first treatment was 40,39 x 106 CFU/gram, and 40,00 x 106 CFU/gram in treatment two. While chicken meat with lemongrass grater was incubated after 24 hours, there was a decrease in the number of colonies in the first treatment of 33,91 x 106 CFU/gram and the second treatment of 34,30 x 106 CFU/gram.Conclusion: There was a decrease in the number of germs in broiler chicken meat given grated lemongrass leaves after 24 hours of incubation.